Surface-acoustic-wave transducers for the extremely-high-frequency range using AlN/SiC(0001) - Takagaki, Y; Hesjedal, T; Brandt, O; Ploog, K (2004)
The fast sound propagation in AlN layers is demonstrated to enable generation of surface acoustic waves (SAWs) by interdigital transducers at a frequency beyond 30 GHz. While scaling down the wavelength of the transducers fabricated on AlN/SiC structures and the thickness of the AlN top layer to raise the operation frequency, the excitation of SAWs becomes intricate due to the weak electromechanical coupling in SiC. We examine the dependence of the feasibility of SAW generation on the AlN layer thickness.